PENGARUH PENGGUNAAN GAMIFIKASI DAN KETERLIBATAN SISWA TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA KELAS Xl BISNIS RITEL PADA MATA PELAJARAN BISNIS RITEL DI SMK NEGERI 13 MEDAN - Ricke Triyani Purba; Muhammad Fitri Rahmadana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the use of gamification and student engagement on the critical thinking skills of grade XI retail business students in the retail business subject at SMK Negeri 13 Medan. This research is a quantitative study with an ex post facto design. The population in this study was grade XI retail business students in the retail business subject at SMK Negeri 13 Medan. The sampling technique used in this study was total sampling with a sample size of 34 students. Data collection techniques consisted of observation sheets and questionnaires. The data analysis technique used was multiple linear regression analysis. The results of this study indicate that: 1) There is a positive and significant effect of the use of gamification and student engagement together on critical thinking skills. This is shown by an F value of 63.046 and a significance level of < 0.05 (0.000 < 0.05). Then, the coefficient of determination (R²) is 0.803 or 80.3%, which means that the use of gamification and student engagement contributes 80.3% to critical thinking skills. 2) There is a positive and significant effect of the use of gamification on critical thinking skills. This is indicated by a calculated t value of 10.391 with a significance level of < 0.05 (0.000 < 0.05). 3) There is a positive and significant effect of student engagement on critical thinking skills. This is shown by a calculated t value of 3.877 with a significance level of < 0.05 (0.001 < 0.05).